Poverty and nutritional status-related intestinal parasitism in students, Huanuco, Peru, 2010 - Berto Moreano, César Gabriel (2013)
Introduction: Studies have reported high prevalence of parasitic disease in students from the jungle although none has associated itwith poverty and nutritional factors. Objectives: To determine the relationship between poverty and nutritional factors with the presenceof intestinal parasites in students from a Huanuco village. Design: Cross-sectional study. Setting: Venenillo hamlet, Huanuco, Peru.Participants: Students from the only school in Venenillo. Interventions: Parasitological examination by Lugol’s iodine direct examinationand Lumbreras' fast sedimentation technique was performed in 42 students. Level of poverty was determined by the unsatisfied basicneeds index and degree of malnutrition by the Waterlow index. Statistical analysis was performed using Goodman and Kruskal’sgamma coefficient. Main outcome measures: Intestinal parasitosis association with poverty and nutritional status. Results: Presence ofintestinal parasites was 97.6%. A strong association was found between parasitism and level of poverty (p=0.02, gamma=0.82). Therewas no significant association between level of malnutrition and parasitism. Conclusions: Association between intestinal parasitosis andpoverty was encountered in the studied population.